MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MUTU PENDIDIKAN PASCA PANDEMI COVID-19 - Nor Fadhilah; Wahab Wahab; Rudiansyah Rudiansyah (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
The current post-Covid-19 pandemic situation requires PAI teachers to re-adapt in the process of teaching and learning activities in class from planning, implementation to the evaluation stage. In fact, from these 3 basic points, is the quality of education from learning management due to the Covid-19 pandemic still holding up like the quality of education before the Covid-19 pandemic. This research used a descriptive qualitative approach with library research. The purpose of this research is to frame and review by describing the planning, implementation and evaluation included in learning management so that the quality of education can be reassessed and improved. The results of the research show that, PAI learning planning with ease of learning objectives, learning materials, learning methods, learning resources and learning evaluation. The implementation of PAI teacher learning carries out several stages starting from the pre-instructional stage (pre-instructional stage), the (instructional stage) and the evaluation stage (evaluation stage). Evaluation of PAI learning is providing practice questions, remedial and enrichment